Injury-induced Autophagy Delays Axonal Regeneration after Optic Nerve Damage in Adult Zebrafish. (21st August 2021) - Beckers, An; Vanhunsel, Sophie; Van Dyck, Annelies; Bergmans, Steven; Masin, Luca; Moons, Lieve
Highlights: ONC triggers autophagy in the retinotectal system of adult zebrafish. Injured RGCs induce autophagy in their soma and regrowing axons. Macroglial cells in the optic nerve/optic tectum display autophagy after ONC. Systemic autophagy inhibition accelerates axonal regeneration. Increased mTOR activity might underlie the positive effect of autophagy inhibition. Abstract: Optic neuropathies comprise a group of disorders in which the axons of retinal ganglion cells (RGCs), the retinal projection neurons conveying visual information to the brain, are damaged. This results in visual impairment or even blindness, which is irreversible as adult mammals lack the capacity to repair or replace injured or lost neurons. Despite intensive research, no efficient treatment to induce axonal regeneration in the central nervous system (CNS) is available yet. Autophagy, the cellular recycling response, was shown repeatedly to be elevated in animal models of optic nerve injury, and both beneficial and detrimental effects have been reported. In this study, we subjected spontaneously regenerating adult zebrafish to optic nerve damage (ONC) and revealed that autophagy is enhanced after optic nerve damage in zebrafish, both in RGC axons and somas, as well as in macroglial cells of the retina, the optic nerve and the visual target areas in the brain. Interestingly, the pattern of the autophagic response in the axons followed the spatiotemporal window of axonal regrowth, which suggests that autophagy is ongoing at the growth cones. Pharmacological inhibition of the recycling pathway resulted in accelerated RGC target reinnervation, possibly linked to increased mechanistic target of rapamycin (mTOR) activity, known to stimulate axonal regrowth. Taken together, these intriguing findings underline that further research is warranted to decipher if modulation of autophagy could be an effective therapeutic method to induce CNS regeneration.